Draft Ninth Five Year Plan (1997-2002) and Annual Plan 1997-98 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1997)
After India became free in 1947 there was a demand in some quarters for the merger of hill States with the east Punjab but it met with vehement opposition from the rulers and people. In what is Himachal Pradesh today, the Praja Mandal workers and the rulers had different opinions about the future of these hilly States. After a brief spell of hectic activities, the rulers and the Praja Mandal workers decided to inform Government of India to form a union of these States with the name of Himachal Pradesh. In view of these events the Central Government decided to integrate all these States into a single unit to be administered by Govt, of India through a Chief Commissioner.
Planning Department, Government of Himachal Pradesh